Improved Design of a Broadband Dielectric Resonator Antenna with Wide Beam - Yan He; Weihua Wang; Hu Yang; Xiangyu Du (International Journal of Antennas and Propagation)
A wide-beam and broadband dielectric resonator antenna (DRA) with broadside pattern is proposed and analyzed. The excellent performance of wide beam is achieved by designing the metal ground. In addition, the antenna has broad bandwidth by introducing an air gap between the dielectric resonator (DR) and the ground. From simulated results, the impedance bandwidth (S11 < −10 dB) of the proposed antenna is about 35%, from 2.8 to 4 GHz, and the maximum 3 dB beam width in H-plane is greater than 210°. A prototype of the proposed DRA is produced and tested. Good agreement between the simulated and measured results is achieved.